If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 90 + -1x = 46 Reorder the terms: 90 + 3x + -1x = 46 Combine like terms: 3x + -1x = 2x 90 + 2x = 46 Solving 90 + 2x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 2x = 46 + -90 Combine like terms: 90 + -90 = 0 0 + 2x = 46 + -90 2x = 46 + -90 Combine like terms: 46 + -90 = -44 2x = -44 Divide each side by '2'. x = -22 Simplifying x = -22
| K=-1/10/3 | | Y[hat]=12.6X+5 | | K=-1/103 | | 16.08+(-2.45)+0.94= | | 48x-56+4=4x+5 | | -5(0.1x+0.2)-1.9=-0.4 | | 6x+12=106 | | 13x-23=o | | 3+4d=49 | | 8(6x-7)+4=4x+5 | | -(-c+4)+5c+9= | | ln(y)=8x+ln(C) | | 420=100t-5t^2 | | 0=r^2-4r+3 | | 7(b-3)+8b=2 | | -5(-4)(-4)(3)= | | 6x(7-2)= | | 4x^4-35x^2=9 | | X+20y-40=0 | | -6(2x+1)=-4x+10 | | (253-x)(2x-x)=0.17 | | -9x+18y=36 | | -9y+18y=36 | | 0=r^2-4r+5 | | 4x-3+x=32 | | 4r=r^2+5 | | 60+9x=10x-2 | | (26-2x)(23-2x)=208 | | 3x-6y-42y-140x= | | 16+3x=4x | | 5ln(t+4)=5 | | (2x+3)(2x^2-13x+20)=0 |